The relationship between coach support and exercise habits on engagement and sports success: A focused study among young table tennis athletes - Ruqayah, Roiyatul; Bafirman; Damrah; Rifatovna, Shakirzyanova Sabina; Setiawan, Edi (UIR Press, 2025)
Background: Engagement and sports success are two important aspects for young athletes in various sports including table tennis, but there is still limited research reporting on factors that can influence these two aspects. Objectives: This study investigates the relationship between coach support and exercise habits with engagement and sports success among young table tennis athletes. Methods: This study adopted a correlational research method to reveal the relationship between each variable. Participants included young table tennis athletes (n = 50), who were assigned to complete questionnaires on coach support, exercise habits, engagement, and sports success. Finding/Results: The study results are as follows. First, a strong positive correlation was observed ranging from r = 0.72* to r = 0.95*, indicating that higher levels of perceived coach support are associated with greater engagement. Meanwhile, correlations ranged from from r = 0.48* to r = 0.87*, indicating a moderate to strong relationship between coach support and sports success. Second, a significant correlation was found, ranging from r = 0.45* to r = 0.92*, demonstrating that consistent exercise habits contribute to higher engagement. Meanwhile, correlations ranged from r = 0.45* to r = 0.87*, indicating a moderate to strong relationship between exercise habits with sports sports. Conclusion: The results highlight the importance of coach support and exercise habits in fostering engagement and enhancing sports success among young table tennis athletes. A limitation of our study is the relatively small number of participants, consisting only of young table tennis athletes. Therefore, we recommend that future research include participants from other sports, such as tennis, badminton, or sepak takraw.